Odpowiedzi

2009-12-16T20:28:20+01:00
A)
2x-2y=7 2x=7+2y x=3,5+y x=4,5
4x+3y=21 4(3,5+y) +3y=21 14+7y=21 7=7y y=1
2009-12-16T20:32:58+01:00
A)
2x-2y=7 /* -2
4x+3y=21

-4x + 4y = -14
4x + 3y = 21
_____________
7y = 7 /:7
y = 1


2x-2y=7 /*3
4x+3y=21 /*2

6x - 6y = 21
8x + 6y = 42
_____________
14x = 21 /:14
x = 1,5



b)
0,4x+0,3y=1,4 /*10
0,1x+3y=2,3 /*10

4x + 3y = 14
x + 30y = 23 /*-4

4x + 3y = 14
-4x - 120y = -92
__________________
-117y = -78 /: - 117
y = 0,(6)



0,4x+0,3y=1,4 /*10
0,1x+3y=2,3 /*10

4x + 3y = 14 /* -10
x + 30y = 23

-40x - 30y = -140
x + 30y = 23

-39x = -117 /: -39
x = 3




c)
2x+3y=14 /*3
3x-2y=8 /* -2

6x + 9y = 42
-6x + 4y = -16
___________
13y = 26 /:13
y = 2




2x+3y=14 /*2
3x-2y=8 /* 3

4x + 6y = 28
9x - 6y = 24
_____________
13x = 52 /:13
x = 4
2009-12-16T20:34:21+01:00
A) 2x-2y=7
4x+3y=21

2x=7+2y
4x+3y=21

4x=14+4y
4x+3y=21

4x=14+4y
14+4y+3y=21

4x=14+4y
7y=7

4x=14+4y
y=1

4x=14+4
y=1

4x=18
y=1

x=4,5
y=1

b)0,4x+0,3y=1,4
0,1x+3y=2,3

4x+3y=14
x+30y=23

4x+3y=14
x=23-30y

4(23-30y)=14
x=23-30y

-120y=14-92
x=23-30y

y=1,5
x=23-30*1,5

y=1,5
x=-22

c)2x+3y=14
3x-2y=8

2x=14-3y
3x-2y=8

6x=42-9y
6x-4y=16

6x=42-9y
42-9y-4y=16

6x=42-9y
-13y=16-42

6x=42-9y
-13y=-26

6x=42-9y
y=2

6x=42-18
y=2

6x=24
y=2

x=4
y=2